Colorectal cancer cells utilize autophagy to maintain mitochondrial metabolism for cell proliferation under nutrient stress - Devenport, Samantha N. (JCI Insight, 2021)
Cancer cells reprogram cellular metabolism to maintain adequate nutrient pools to sustain proliferation. Moreover, autophagy is a regulated mechanism to break down dysfunctional cellular components and recycle cellular nutrients. However, the requirement for autophagy and the integration in cancer cell metabolism is not clear in colon cancer. Here, we show a cell-autonomous dependency of autophagy for cell growth in colorectal cancer. Loss of epithelial autophagy inhibits tumor growth in both sporadic and colitis-associated cancer models. Genetic and pharmacological inhibition of autophagy inhibits cell growth in colon cancer–derived cell lines and patient-derived enteroid models. Importantly, normal colon epithelium and patient-derived normal enteroid growth were not decreased following autophagy inhibition. To couple the role of autophagy to cellular metabolism, a cell culture screen in conjunction with metabolomic analysis was performed. We identified a critical role of autophagy to maintain mitochondrial metabolites for growth. Loss of mitochondrial recycling through inhibition of mitophagy hinders colon cancer cell growth. These findings have revealed a cell-autonomous role of autophagy that plays a critical role in regulating nutrient pools in vivo and in cell models, and it provides therapeutic targets for colon cancer.